2014
DOI: 10.1093/jnci/dju062
|View full text |Cite
|
Sign up to set email alerts
|

Role in Tumor Growth of a Glycogen Debranching Enzyme Lost in Glycogen Storage Disease

Abstract: Using an in vivo RNA interference screen, we discovered that AGL, a glycogen debranching enzyme, has a biologically and statistically significant role in suppressing human cancer growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
105
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(111 citation statements)
references
References 35 publications
6
105
0
Order By: Relevance
“…Despite the understanding of AGL in both glycogenolysis and in GSD III, the present authors were the first to report a connection between AGL and bladder cancer (9,12). Analysis of bladder tumors from patients demonstrated that loss of AGL expression (gene and protein) in cancer has been associated with clinically aggressive tumor prognosis and poor patient mortality (9).…”
Section: Involvement Of Glycogen Debranching Enzyme In Bladder Cancermentioning
confidence: 76%
See 4 more Smart Citations
“…Despite the understanding of AGL in both glycogenolysis and in GSD III, the present authors were the first to report a connection between AGL and bladder cancer (9,12). Analysis of bladder tumors from patients demonstrated that loss of AGL expression (gene and protein) in cancer has been associated with clinically aggressive tumor prognosis and poor patient mortality (9).…”
Section: Involvement Of Glycogen Debranching Enzyme In Bladder Cancermentioning
confidence: 76%
“…Tumor cells expressing low levels of AGL displayed enhanced anchorage independent and dependent growth, while AGL overexpression decreased anchorage independent and dependent growth (9). Further analysis of AGL low tumor cells presented increased production of limit dextrin, or abnormally branched glycogen, similar to patients with GSD III.…”
Section: Agl Glycogen Metabolism and Regulation Of Glycine Synthesismentioning
confidence: 89%
See 3 more Smart Citations